Review and comparison of linear algorithms to quantify muscle fatigue based on sEMG signals - Coraggio, Giorgia; Cera, Mattia; Cirelli, Marco; Valentini, Pier Paolo (Ergonomics, 2024)
Surface electromyography techniques are widely used in field of motion analysis and ergonomics combining precise muscular activation assessment with low-invasiveness and wearability. The aim of this investigation is to identify the myoelectrical manifestations of fatigue and to compare the effectiveness of sEMG-based quantitative indices for fatigue assessment. The investigated indexes are the ARV and RMS signal amplitudes, the mean frequency, the median frequency, the Dimitrov index, the instantaneous mean frequency and Wavelet distribution-based WIRE51 index. Two different protocols were developed, and the activity of the lateral deltoid and middle trapezius muscles was recorded. The WIRE51 index is found to have the highest sensitivity in the detection of the difference between the repetitions of each exercise for both protocols. Due to the lack of a unified standard for the performance comparison of fatigue indices, a correlation analysis was carried out between the result provided by the indices and the subjective fatigue perception employing the RPE scale. The aim of this study is to compare quantitative indices for assessing muscular fatigue from the sEMG acquisitions. The assessment is accomplished with an experimental investigation of ten subjects and two repetitive movement types. The best performing indices are found to be the WIRE51 and the Dimitrov ones.